The archaeology of the logging industry - Franzen, John G. (American experience in archaeological perspective., 2020)
"In this book, John Franzen surveys archaeological studies of logging sites across the nation from the nineteenth and twentieth centuries, explaining how material evidence found at these locations illustrates key aspects of the American experience during this era"--